Beyond cloud cover: Low- and high-altitude clouds have distinct impacts on tree sap flow and transpiration - Sini Talvinen; Yann Salmon; Jose Gutierrez Lopez; Maj-Lena Finnander Linderson; Štěpánka Řehořková; Ladislav Šigut; Abhay Devasthale; Ilona Ylivinkka; Caroline Greiser; Ekaterina Ezhova; Johannes Quaas; Natalia Kowalska; et al. (Agricultural and Forest Meteorology, 2026)

Bark beetles as microclimate engineers – thermal characteristics of infested spruce trees at the canopy surface and below the canopy - Caroline Greiser; Langning Huo; Mark Ghaly; Ian Brown; Christophe Metsu; Koenraad Van Meerbeek; Philipp Lehmann (Agricultural and Forest Meteorology, 2025)

Proximal microclimate: Moving beyond spatiotemporal resolution improves ecological predictions - David H. Klinges; J. Alex Baecher; Jonas J. Lembrechts; Ilya M. D. Maclean; Jonathan Lenoir; Caroline Greiser; Michael Ashcroft; Luke J. Evans; Michael R. Kearney; Juha Aalto; Isabel C. Barrio; Pieter De Frenne; et al. (Global Ecology and Biogeography, 2024)
Aim The scale of environmental data is often defined by their extent (spatial area, temporal duration) and resolution (grain size, temporal interval). Although describing climate data scale via these terms is appropriate for most meteorological applications, for ecology and biogeography, climate data of the same spatiotemporal resolution and extent may differ in their relevance to an organism. Here, we propose that climate proximity, or how well climate data represent the actual conditions that an organism is exposed to, is more important for ecological realism than the spatiotemporal resolution of the climate data. Location Temperature comparison in nine countries across four continents; ecological case studies in Alberta (Canada), Sabah (Malaysia) and North Carolina/Tennessee (USA). Time Period 1960–2018. Major Taxa Studied Case studies with flies, mosquitoes and salamanders, but concepts relevant to all life on earth. Methods We compare the accuracy of two macroclimate data sources (ERA5 and WorldClim) and a novel microclimate model ( microclimf ) in predicting soil temperatures. We then use ERA5, WorldClim and microclimf to drive ecological models in three case studies: temporal (fly phenology), spatial (mosquito thermal suitability) and spatiotemporal (salamander range shifts) ecological responses. Results For predicting soil temperatures, microclimf had 24.9% and 16.4% lower absolute bias than ERA5 and WorldClim respectively. Across the case studies, we find that increasing proximity (from macroclimate to microclimate) yields a 247% improvement in performance of ecological models on average, compared to 18% and 9% improvements from increasing spatial resolution 20‐fold, and temporal resolution 30‐fold respectively. Main Conclusions We propose that increasing climate proximity, even if at the sacrifice of finer climate spatiotemporal resolution, may improve ecological predictions. We emphasize biophysically informed approaches, rather than generic formulations, when quantifying ecoclimatic relationships. Redefining the scale of climate through the lens of the organism itself helps reveal mechanisms underlying how climate shapes ecological systems.

Microclimate, an important part of ecology and biogeography - Julia Kemppinen; Jonas J. Lembrechts; Koenraad Van Meerbeek; Jofre Carnicer; Nathalie Isabelle Chardon; Paul Kardol; Jonathan Lenoir; Daijun Liu; Ilya Maclean; Jan Pergl; Patrick Saccone; Rebecca A. Senior; et al. (Global Ecology and Biogeography, 2024)
Brief introduction: What are microclimates and why are they important? Microclimate science has developed into a global discipline. Microclimate science is increasingly used to understand and mitigate climate and biodiversity shifts. Here, we provide an overview of the current status of microclimate ecology and biogeography in terrestrial ecosystems, and where this field is heading next. Microclimate investigations in ecology and biogeography We highlight the latest research on interactions between microclimates and organisms, including how microclimates influence individuals, and through them populations, communities and entire ecosystems and their processes. We also briefly discuss recent research on how organisms shape microclimates from the tropics to the poles. Microclimate applications in ecosystem management Microclimates are also important in ecosystem management under climate change. We showcase new research in microclimate management with examples from biodiversity conservation, forestry and urban ecology. We discuss the importance of microrefugia in conservation and how to promote microclimate heterogeneity. Methods for microclimate science We showcase the recent advances in data acquisition, such as novel field sensors and remote sensing methods. We discuss microclimate modelling, mapping and data processing, including accessibility of modelling tools, advantages of mechanistic and statistical modelling and solutions for computational challenges that have pushed the state‐of‐the‐art of the field. What's next? We identify major knowledge gaps that need to be filled for further advancing microclimate investigations, applications and methods. These gaps include spatiotemporal scaling of microclimate data, mismatches between macroclimate and microclimate in predicting responses of organisms to climate change, and the need for more evidence on the outcomes of microclimate management.

Higher soil moisture increases microclimate temperature buffering in temperate broadleaf forests - Caroline Greiser; Lucia Hederová; Giulia Vico; Jan Wild; Martin Macek; Martin Kopecký (Agricultural and Forest Meteorology, 2024)

ForestClim —Bioclimatic variables for microclimate temperatures of European forests - Stef Haesen; Jonas J. Lembrechts; Pieter De Frenne; Jonathan Lenoir; Juha Aalto; Michael B. Ashcroft; Martin Kopecký; Miska Luoto; Ilya Maclean; Ivan Nijs; Pekka Niittynen; Johan van den Hoogen; et al. (Global Change Biology, 2023)
Microclimate research gained renewed interest over the last decade and its importance for many ecological processes is increasingly being recognized. Consequently, the call for high‐resolution microclimatic temperature grids across broad spatial extents is becoming more pressing to improve ecological models. Here, we provide a new set of open‐access bioclimatic variables for microclimate temperatures of European forests at 25 × 25 m 2 resolution.

Climate adaptation of biodiversity conservation in managed forest landscapes - Kristoffer Hylander; Caroline Greiser; Ditte M. Christiansen; Irena A. Koelemeijer (Conservation Biology, 2022)
Conservation of biodiversity in managed forest landscapes needs to be complemented with new approaches given the threat from rapid climate change. Most frameworks for adaptation of biodiversity conservation to climate change include two major strategies. The first is the resistance strategy, which focuses on actions to increase the capacity of species and communities to resist change. The second is the transformation strategy and includes actions that ease the transformation of communities to a set of species that are well adapted to the novel environmental conditions. We suggest a number of concrete actions policy makers and managers can take. Under the resistance strategy, five tools are introduced, including: identifying and protecting forest climate refugia with cold‐favored species; reducing the effects of drought by protecting the hydrological network; and actively removing competitors when they threaten cold‐favored species. Under the transformation strategy, we suggest three tools, including: enhancing conditions for forest species favored by the new climate, but currently disfavored by forest management, by planting them at suitable sites outside their main range; and increasing connectivity across the landscape to enhance the expansion of warm‐favored species to sites that have become suitable. Finally, we suggest applying a landscape perspective and simultaneously managing for both retreating and expanding species. The two different strategies (resistance and transformation) should be seen as complementary ways to maintain a rich biodiversity in future forest ecosystems.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

ForestTemp – Sub‐canopy microclimate temperatures of European forests - Stef Haesen; Jonas J. Lembrechts; Pieter De Frenne; Jonathan Lenoir; Juha Aalto; Michael B. Ashcroft; Martin Kopecký; Miska Luoto; Ilya Maclean; Ivan Nijs; Pekka Niittynen; Johan van den Hoogen; et al. (Global Change Biology, 2021)
Ecological research heavily relies on coarse‐gridded climate data based on standardized temperature measurements recorded at 2 m height in open landscapes. However, many organisms experience environmental conditions that differ substantially from those captured by these macroclimatic (i.e. free air) temperature grids. In forests, the tree canopy functions as a thermal insulator and buffers sub‐canopy microclimatic conditions, thereby affecting biological and ecological processes. To improve the assessment of climatic conditions and climate‐change‐related impacts on forest‐floor biodiversity and functioning, high‐resolution temperature grids reflecting forest microclimates are thus urgently needed. Combining more than 1200 time series of in situ near‐surface forest temperature with topographical, biological and macroclimatic variables in a machine learning model, we predicted the mean monthly offset between sub‐canopy temperature at 15 cm above the surface and free‐air temperature over the period 2000–2020 at a spatial resolution of 25 m across Europe. This offset was used to evaluate the difference between microclimate and macroclimate across space and seasons and finally enabled us to calculate mean annual and monthly temperatures for European forest understories. We found that sub‐canopy air temperatures differ substantially from free‐air temperatures, being on average 2.1°C (standard deviation ± 1.6°C) lower in summer and 2.0°C higher (±0.7°C) in winter across Europe. Additionally, our high‐resolution maps expose considerable microclimatic variation within landscapes, not captured by the gridded macroclimatic products. The provided forest sub‐canopy temperature maps will enable future research to model below‐canopy biological processes and patterns, as well as species distributions more accurately.

Forest microclimates and climate change: Importance, drivers and future research agenda - Pieter De Frenne; Jonathan Lenoir; Miska Luoto; Brett R. Scheffers; Florian Zellweger; Juha Aalto; Michael B. Ashcroft; Ditte M. Christiansen; Guillaume Decocq; Karen De Pauw; Sanne Govaert; Caroline Greiser; et al. (Global Change Biology, 2021)
Forest microclimates contrast strongly with the climate outside forests. To fully understand and better predict how forests' biodiversity and functions relate to climate and climate change, microclimates need to be integrated into ecological research. Despite the potentially broad impact of microclimates on the response of forest ecosystems to global change, our understanding of how microclimates within and below tree canopies modulate biotic responses to global change at the species, community and ecosystem level is still limited. Here, we review how spatial and temporal variation in forest microclimates result from an interplay of forest features, local water balance, topography and landscape composition. We first stress and exemplify the importance of considering forest microclimates to understand variation in biodiversity and ecosystem functions across forest landscapes. Next, we explain how macroclimate warming (of the free atmosphere) can affect microclimates, and vice versa, via interactions with land‐use changes across different biomes. Finally, we perform a priority ranking of future research avenues at the interface of microclimate ecology and global change biology, with a specific focus on three key themes: (1) disentangling the abiotic and biotic drivers and feedbacks of forest microclimates; (2) global and regional mapping and predictions of forest microclimates; and (3) the impacts of microclimate on forest biodiversity and ecosystem functioning in the face of climate change. The availability of microclimatic data will significantly increase in the coming decades, characterizing climate variability at unprecedented spatial and temporal scales relevant to biological processes in forests. This will revolutionize our understanding of the dynamics, drivers and implications of forest microclimates on biodiversity and ecological functions, and the impacts of global changes. In order to support the sustainable use of forests and to secure their biodiversity and ecosystem services for future generations, microclimates cannot be ignored.

Hiding from the climate: Characterizing microrefugia for boreal forest understory species - Caroline Greiser; Johan Ehrlén; Eric Meineri; Kristoffer Hylander (Global Change Biology, 2020)
Climate warming is likely to shift the range margins of species poleward, but fine‐scale temperature differences near the ground (microclimates) may modify these range shifts. For example, cold‐adapted species may survive in microrefugia when the climate gets warmer. However, it is still largely unknown to what extent cold microclimates govern the local persistence of populations at their warm range margin. We located 99 microrefugia, defined as sites with edge populations of 12 widespread boreal forest understory species (vascular plants, mosses, liverworts and lichens) in an area of ca. 24,000 km 2 along the species' southern range margin in central Sweden. Within each population, a logger measured temperature eight times per day during one full year. Using univariate and multivariate analyses, we examined the differences of the populations' microclimates with the mean and range of microclimates in the landscape, and identified the typical climate, vegetation and topographic features of these habitats. Comparison sites were drawn from another logger data set ( n = 110), and from high‐resolution microclimate maps. The microrefugia were mainly places characterized by lower summer and autumn maximum temperatures, late snow melt dates and high climate stability. Microrefugia also had higher forest basal area and lower solar radiation in spring and autumn than the landscape average. Although there were common trends across northern species in how microrefugia differed from the landscape average, there were also interspecific differences and some species contributed more than others to the overall results. Our findings provide biologically meaningful criteria to locate and spatially predict potential climate microrefugia in the boreal forest. This opens up the opportunity to protect valuable sites, and adapt forest management, for example, by keeping old‐growth forests at topographically shaded sites. These measures may help to mitigate the loss of genetic and species diversity caused by rear‐edge contractions in a warmer climate.

A preliminary assessment of landscape features and cultural practices of sacred fresh water swamps in the central Western Ghats, India - Narasimha Hegde; Rafael Ziegler; Caroline Greiser; Hans Joosten (Wetlands Ecology and Management, 2018)